Pest Analysis Dalam Upaya Pencapaian Target Anggaran Belanja Pegawai Di Kabupaten Kediri - Hartono, Doni Hendra; Askafi, Eka; Daroini, Ahsin (Otonomi, 2026)
This study analyzes the application of PEST Analysis to achieve the employee expenditure target in Kediri Regency, as mandated by Law no. 1 of 2022 concerning Central and Regional financial relations, which caps employee spending at 30% of total regional expenditure. A qualitative case study located in Kediri regency design was employed with key informants from BAPPEDA, BKAD, BKPSDM, BAPENDA, Dinas Komunikasi dan Informatika, Bagian Organisasi Region Secretarary and community representatives. Data were collected through in‑depth interviews, observation, and documentation, and analyzed via PEST factor identification, impact assessment, opportunity–threat classification, EFAS prioritization, and strategy formulation. Findings indicate that political (regulatory support, leadership commitment), economic (intergovernmental transfers, local revenue dynamics), social (public service expectations, digital literacy), and technological (e‑government adoption) factors shape policy effectiveness. Key strategies include performance‑based institutional and HR reforms, local revenue optimization, and digital transformation to reach the 30% target without undermining service quality